Landscape-ecological diversity of the territory of Poltava region - Pysarenko , P. V.; Samoilik , M. S.; Dychenko , O. Yu. (Scientific Progress & Innovations, 2019)
The purpose of the article is to study and determine the types of land use and indicators of landscape and ecological diversity of the territory of Poltava region according to the data of the remote sensing of the Earth (Global Land Cover 2000 Project). Methods of research. The method of analysis of the Earth remote sensing data (GLC 2000) was used to determine the types of land use within the studied area. The research results. The data on the landscape-ecological diversity of the cover types in Poltava region according to the data of remote sensing of the Earth have been given in the article. As a result of the conducted research and corresponding calculations it has been established that the largest landscape and ecological diversity is characteristic for the eastern and central districts of Poltava region. It is the most characteristic of Reshetylivka and Velyka Bahachka districts located in the center of the studied area, while the lowest indicators of landscape diversity were found in Chornukhy, Semenivka, Hlobyno and Kobeliaky districts. The level of landscape diversity in Poltava region is primarily determined by the ratio of agro-ecosystems to landscape complexes of other types. The elements of scientific novelty. The assessment of the landscape and ecological diversity of Poltava region has been carried out and its dynamics based on the data of MODIS remote sensing of the Earth's surface has been studied. Practical significance. The analysis of the cover types of the Earth's surface within Poltava region has shown significant plowing of the territory and its occupation with agro-ecosystems. Landscape diversity was formed at the expense of arable land, territories with a mosaic of arable land, grassland and the areas with spaced vegetation cover. The components of natural ecosystems were concentrated in river floodplains of the region and are represented by floodplain forests, meadows and swamps.